Effects of Organized Auditory Stimulation by Familiar Voice on Blood Pressure and Body Temperature in Comatose Patients - Mohammad Kazem Mohammadi; Mohammad Reza Yeganeh Rasteh Kenari; Tahereh Khaleghdoost Mohammadi; Zahra Atrkare Roshan; Ayda Mohammad Ebrahimzadeh (Guilan University of Medical Sciences, 2017)
Introduction: Brain injury induced coma is the main cause of hospitalization of patients in the intensive care unit (ICU) and their consequent stressful physiological complications, which can be prevented using sensory stimulation as a therapeutic method. Nevertheless, identifying and using the optimal sensory stimulation program is crucial. Objective: The present study was conducted to determine the effects of organized auditory stimulation by familiar voice on blood pressure and body temperature in patients admitted to ICUs. Materials and Methods: The present clinical trial was conducted on 60 comatose patients with traumatic brain injury (TBI) admitted to the ICU of Poursina Teaching Hospital, Rasht, Iran. The patients were randomly assigned to the intervention group (N=30) and the control group. In the intervention group, auditory stimulation was conducted using significant others voices in three consecutive evening shifts, 10 minutes each time. Blood pressure and body temperature were evaluated using a checklist, and the findings obtained were analyzed using ANOVA, the t-test and the Chi-square test. Results: The results obtained revealed significant differences in the mean blood pressure and body temperature before and after auditory stimulation in the intervention group (P<0.001), while these differences were insignificant in the controls. The two groups were also found to be insignificantly different in terms of the three-day variations in the mean blood pressure and the mean body temperature. Conclusion: Given the significant effects of auditory stimulation on hemodynamic indicators, auditory stimulation by familiar voice is recommended in comatose patients admitted to ICUs through face-to-face visits with their family members or by playing their recorded voice. uld also be designed to provide the patients with counseling services. level of empathy diminished with a higher level of father's education (β=-0.142). Conclusion: The results obtained showed no significant difference between first- and final-year students in terms of empathy score. Since reinforcing predicting factors leads to greater student empathy with patients, empathy skills education in the course of study and generating interest among students appears to increase their sense of empathy